Methodology for the isolation, identification and selection of Bacillus spp. strains for the preparation of animal additives - Milián, Grethel; Rondón, Ana J.; Pérez, M.; Arteaga, Fátima; Bocourt, R.; Portilla, Yadileiny; Rodríguez, Marlen; Pérez, Y.; Beruvides, A.; Laurencio, M. (Cuban Journal of Agricultural Science, 2017)
A methodology for the isolation, identification and selection of Bacillus spp. strains is established for probiotic purposes for their use in livestock interest. The strains were isolated from different ecosystems (bovine feces, caecum bird, decayed tomato juice and soil with slaughterhouse blood). The experiment was developed in three stages. The first one was related to the isolation, preselection and identification of the strains and conservation; the second with the evaluation of the growth capacity in a new culture medium, formulated from some national components (final molasses, Saccharomyces cerevisiae yeast cream hydrolyzate, calcium chloride and bacteriological peptone); the third stage included the integral evaluation of the effect of animal additives on probiotic response indicators in birds. With the proposed methodology, 100 strains were isolated, 48 of them with characteristics of the Bacillus spp. genus. The three strains were characterized (C-31, C-34 and E-44) that had the best characteristics as candidates for probiotics, capable of manifesting high growth capacity (P <0.001) in the new culture medium. The production cost of them was 2.34 Cuban pesos and 0.54 / L USD. These three animal additives showed their effect on chickens, when improving the probiotic response in the microbiological, immunological, fermentative, hematological and productive indicators in these animals. From the obtained results, it can be assured that the methodological proposal to isolate, identify and select Bacillus spp. strains can be applied in Cuba to improve the productive response in livestock interest. Key words: methodology, probiotics, bacilli